Trends and challenges of Chinese-Polish translation and interpretation industry in Poland - Kupś, Hanna; Burkiewicz, Kamil (Lingua Posnaniensis, 2020)
China is Poland’s largest Asian trade partner. Increased trade in recent years, combined with a visible growth of interest in Asian cultures, has contributed to the development of the Polish translation industry, especially in the Polish-Chinese language pair. Although the number of sworn translators registered with the Ministry of Justice remains small (16), the dynamic increase in the number of people dealing with regular translations makes similar services more and more available. The article aims to outline the general situation of Chinese translators in Poland. The methodological basis of the article is a survey conducted in August 2018, in which 67 respondents took part, who declared themselves translators in the aforementioned pair of languages. The survey consisted of 17 questions to which one or more answers could be given. Respondents were asked about the most frequently translated content, aids, and materials used at work, as well as the particularly difficult topics. The image that emerges from these data allows an assessment of the maturity of the industry and the prospects for its further development.